Kandungan Chrom (Cr6+) dan SENG (Zn) pada Air dan Ikan Puyau (Osteochillus hasselti) di Perairan Sungai Alalak Kawasan Berangas Barat Kabupaten Barito Kuala - Halang, Bunda; Susanti, Evi (bionature, 2019)
Abstract. One of the pollutants that have the potential to pollute rivers and aquatic biota is heavy metals due to community activities around the river. This study aims to determine how the content of Cr6 + and Zn in water and meat of Puyau fish found in the Alalak River, West Berangas Region. This research is a descriptive study with a type of survey research. Water sampling is done using a Kemmerer water sampler and fish sampling using a fishing rod. Tests of Cr6 + and Zn content in water were carried out at the Banjarmasin Health Laboratory and the Cr6 + and Zn content were carried out at the Banjarbaru MIPA basic Laboratory using Atomic Absorption Spectrophotometry (AAS). The results showed an average Cr6 + content in Alalak River waters was 0.11275 mg / L and Zn was 0.0658 mg / L. The content of Cr6 + and Zn has exceeded the quality standard threshold (0.05 mg / L) that has been determined based on South Kalimantan Governor Regulation No.5 of 2007 concerning river quality standards. The average Cr content in Puyau fish meat was 21.415 mg / Kg and Zn was 46.0175 mg / Kg. The Cr6 + and Zn content in Puyau fish has also exceeded the threshold (0.05 mg / Kg; 0.1 / mg / Kg) determined by the DirectorGeneral of POM No. 03725 / SK / VII / 1989. The community is expected to not often consume puyau fish found in the waters of the Alalak River because its Cr6 + and Zn content have exceeded the required threshold. Keywords: krom6 +, seng, alalak river, puyau fish.